Analysis of Factors Affecting The Acceptance and Use of Kompas ePaper by Kompas Daily Newspaper readers using Unified Theory of Acceptance and Use of Technology (UTAUT) Framework - Melissa Sancaka (Jurnal Strategi Pemasaran, 2014)
This research aims to analyze the factors that influence the use of Kompas ePaper by using Unified Theory of Acceptance and Use of Technology (UTAUT). This study will be conducted by distributing questionnaires to 125 Kompas ePaper readers. Analysis techniques that will be used are quantitative analysis with path analysis method and partial least square. The result showed that performance expectancy and effort expectancy have significant influence on behavioral intention Furthermore, facilitating conditions has also significant influence on use behavior